Alokasi Situs-Situs Arkeologi Di Kawasan DAS Way Sekampung - Rr. Triwurjani (Berkala Arkeologi, 1995)
When sorted from upstream to downstream, the Sekampung River extends from South Lampung to Central Lampung. Several archaeological remains found in the upstream area include: Batu Bedil Megalithic Complex. Batu Gajah, and also Fort Tanah. Whereas in the middle there are Bukit Wungkal (Silitonga) sites, Kampung Tua, Bentang Pejambon, Sidomukti Megalithic site. Whereas in the downstream area there is the Pogung Raharjo Megalithic complex, Benteng Sari, Benteng Perigi, Benteng Gedik, Benteng Cicilik, ancient tombs from the Islamic era, the Bumpo stone inscription and other loose finds such as foreign (Chinese) ceramics and local ceramics, stone tools and other artifacts.